Bio-based and biodegradable polymers - State-of-the-art, Challenges and Emerging Trends - Rameshkumar, Saranya; Padamati, Ramesh (My University, 2019)
Frontiers of bio-based and biodegradable polymers are constantly expanding in a view to achieve sustainability. Hence, designing sustainable bioplastics made of either bio-based or biodegradable polymers opens up opportunities to overcome resource depletion and plastic pollution. This review presents a broad perspective on state-of-the-art technologies in bioplastics manufacturing along with the challenges underlying its production, application and post-consumer waste management. Recent scientific advances are catalysing the sustainable design of bioplastics to overcome the present challenges of plastic waste and emerging end-of-life options are contributing to circular economy. As research insights on developing sustainable bioplastics are rapidly evolving, its production and waste management approaches are not only confined to those discussed in this review.
IN_PRESS
Keywords: Sustainability; Biodegradable polymers; Bioplastics; Circular economy; Nanoscience & Materials; Smart & Sustainable Planet